2022
DOI: 10.1001/jamanetworkopen.2022.11889
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Smartphone-Based Financial Incentives on Peripartum Smoking Among Pregnant Individuals

Abstract: Cigarette smoking during pregnancy can cause serious adverse pregnancy, birth, and longer-term health outcomes. 1,2 The most efficacious smoking cessation intervention for peripartum individuals is abstinence-contingent financial incentives (FIs), but there are challenges to scaling this intervention, including reaching individuals in geographically remote areas while retaining treatment efficacy. 3,4 To address that challenge, this study examined the efficacy of a smartphone-based intervention whereby smoking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…Unlike other trials, acceptability of financial incentives to pregnant women and health professionals from recorded interviews24 was examined along with cost effectiveness 2728. Two contemporary US trials4041 showed similar cessation improvements when financial incentives were added to Best Practice defined by the Centres for Disease Control. The first also examined cost effectiveness 42.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other trials, acceptability of financial incentives to pregnant women and health professionals from recorded interviews24 was examined along with cost effectiveness 2728. Two contemporary US trials4041 showed similar cessation improvements when financial incentives were added to Best Practice defined by the Centres for Disease Control. The first also examined cost effectiveness 42.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, a Cochrane review identified 33 randomized controlled trials (RCTs) investigating the effect of financial incentives [ 3 ]. Since then, several other RCTs have confirmed that incentives are an efficient, cheap, and safe method to improve quit rates [ 4 , 20 , 21 , 22 , 23 , 24 , 25 ]. Results from several studies indicate that offering small financial incentives for smoking abstinence are also efficient in disadvantaged persons [ 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pilot trials found similar results among smokers with attention-deficit hyperactivity disorder (Dan et al, 2016), homeless adults (Carpenter et al, 2015), adolescents (Kong et al, 2017), and regular smokers (Alessi et al, 2017; Dallery et al, 2021). Using remote methods and enrolling pregnant women from 33 states ( n = 90), a digital CM program for peripartum smoking resulted in a four-fold increase in abstinence at 24 weeks compared to best practices (Kurti et al, 2022). This study also incorporated a transition from breath CO during the first week of treatment to a salivary cotinine procedure thereafter (cotinine is a metabolite of nicotine).…”
Section: Technology To Promote Access To High-fidelity CMmentioning
confidence: 99%